THE ROLE OF FEEDBACK IN ONLINE WRITING PLATFORMS DENAU INSTITUTE OF ENTREPRENEURSHIP AND PEDAGOGY (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the digital era, online writing platforms have revolutionized how people create, share, and improve their writing. Feedback, a crucial component of the writing process, enhances skill development, engagement, and motivation. This paper examines the role of feedback in online writing platforms, exploring its types, effectiveness, challenges, and strategies for maximizing learning outcomes. The study draws on research evidence, case studies, and practical examples to demonstrate how feedback influences writers’ progress.